The importance of menu variety experience for public health sustainability at higher education institution - Ismail, Sarimah; Kadir, Normah; Pusiran, Arif Kamisan; Zen, Irina Safitri; Khan, Aqeel (Indian Journal of Public Health Research and Development, 2019)
The importance of menu variety from the perspective of public health has lacked of discussion in the literature in comparison to the profit perspective of a foodservice business. This paper reports finding of a research on the importance of menu variety for the sustainability of public health at higher education institution (HEI) from students perspective. Direct observation towards food displayed on the buffet counter of the cafeterias and interview sessions with students were conducted to identify attributes of menu variety as constructs for a survey research. Complete set of 375 questionnaires were collected among students as customer of 20 food outlets at 11 cafeterias of the HEI. Validity value of the questionnaire was 0.98, that analysed by Rasch Development Model. Survey data was analysed using discriptive statistics. Overall mean value for menu variety attributes was 1.97 and standard devition, 0.656, which at the moderate level. This study suggested for the cafeteria food providers, customers and the HEI food autorithy to ensure high level of menu variety is offered to sustain public health of the HEI, customer satisfaction and long tender period of the cafeterias as a food provider.